Antibacterial efficacy of the seed extracts of Melia azedarach against some hospital isolated human pathogenic bacterial strains - Ahmed, Qamar Uddin (Asian Pacific Journal of Tropical Biomedicine, 2011)
Objective: To investigate the antibacterial potential of the polar and non-polar extracts of the seeds of Melia azedarach (M. azedarach) L. (Meliaceae) against eighteen hospital isolated human pathogenic bacterial strains. Methods: Petrol, benzene, ethyl acetate, methanol, and aqueous extracts at five different concentrations (1, 2, 5, 10 and 15 mg/mL) were evaluated. Disk diffusion method was followed to evaluate the antibacterial efficacy. Results: All extracts of the seeds demonstrated significant antibacterial activity against tested pathogens. Among all extracts, ethyl acetate extract revealed the highest inhibition comparatively. The present study also favored the traditional uses reported earlier. Conclusions: Results of this study strongly confirm that the seed extracts of M. azedarach could be effective antibiotics, both in controlling gram-positive and gram-negative human pathogenic infections.